Pengaruh Faktor Pertumbuhan Ekonomi, Jumlah Serapan Kerja dan Upah Minimum Regional Terhadap Ketimpangan Pendapatan - saputri, eva okti; Setyanto, Alief Rakhman (Jurnal Ekonomika : INDEPENDEN, 2023)
Economic growth is an important part for each region. Economic growth in Lampung Province, as measured by GRDP, has continued to increase, fluctuating labor force conditions have not been able to guarantee people's welfare, and the UMR which continues to increase can meet the minimum living needs of the community. The Gini Ratio is an indicator to measure the economic disparity of a region. The formulation of the problem in this study is whether economic growth, employment and regional minimum wages significantly affect economic inequality either partially or simultaneously and from an Islamic economic perspective. This study aims to determine the effect of the three factors, namely economic growth, employment and regional minimum wages on economic inequality partially or simultaneously and in an Islamic economic perspective. The research method used is a quantitative research approach using secondary data in the 2018-2022 observation period. Data collected using the method of documentation from related agencies. Overall the results of multiple linear regression analysis and hypothesis testing can be concluded that simultaneously (Test F) GRDP, Labor and UMR have a significant effect on economic inequality with the results of Fcount being greater than Ftable (55.739 > 4.76) and the sig. 0.000 < 0.05. And partially GRDP has a significant effect on tcount greater than ttable (2.886 > 2.57058) and the value of Sig. (0.001 < 0.05), work absorption has no significant effect tcount is smaller than ttable (-0.385 <2.57058) and the value of Sig. (0.716 > 0.05) and UMR has a significant effect on tcount greater than ttable (2.576 > 2.57058) and the value of Sig. (0.000 <0.05). In the Islamic economic perspective, GRDP is a picture of the economic welfare of society and every human being is obliged to provide a little sustenance obtained through zakat, shadaqah, endowments, etc. so that income distribution is more equitable and reduces inequality, to improve people's welfare in Islamic Economics every Muslim is required to work and fulfill their economic needs so that poverty does not occur, as well as with each region having to set a good minimum wage, it can be concluded that wages must be sufficient, not too low for workers and not too high for entrepreneurs. Keywords: economic growth, UMR, income inequality, total employment, GRDP